Reconstructing middle to late Holocene palaeogeographies of the lower Messenian plain (southwestern Peloponnese, Greece): Coastline migration, vegetation history and sea level change (Palaeogeography, Palaeoclimatology, Palaeoecology, 2009)
The glacio-eustatic sea level rise after the Last Glacial Maximum (LGM) led to a worldwide ﬂooding of shelf areas and the evolution of marine embayments and indentations. Its signiﬁcant deceleration in midHolocene times resulted in the overcompensation by sediment yields and shoreline progradation in many areas. At the southeastern part of the lower Messenian plain (southwestern Peloponnese, Greece) detailed investigations of the Holocene stratigraphy revealed a maximum landward shoreline displacement around 3000 BC. Subsequently, aggradational processes started to form a prominent beach ridge in the late 3rd millennium BC. This is the substratum on which the early Iron Age Poseidon Sanctuary of Akovitika was founded approx. 900–850 BC. Palaeogeographic reconstructions based on 18 corings in the sanctuary and its surroundings revealed the later extension of adjacent marshland and gradual surface levelling due to seasonal inundations. These ﬁndings represent probable reasons for the abandonment of the ceremonial site around 380–350 BC. Palynological studies of the vegetational changes provide evidence for early land use and reﬂect regional settlement activities. Initial degradation and burning of woodland during late Neolithic times (c. 3500–3100 BC) as well as signiﬁcantly reduced human impact during the Protogeometric Dark Ages (c. 1060–900 BC) are proven. Additionally, local relative mean sea level (RSL) change since 5000 BC was reconstructed based on 14 C dated paralic peats.